Network Externalities and Dollarization Hysteresis : The Case of Russia - Oomes, Nienke (IMF Working Papers; Working Paper ;, 2003)
Dollarization in Russia increased rapidly during the early 1990s, but failed to come down in the second half of the 1990s in spite of exchange rate stabilization. To explain this "dollarization hysteresis," this paper develops a model in which network externalities in the demand for currency can generate multiple stable steady states for the dollarization ratio. The model is estimated using a new source of data on dollar currency holdings in Russia. On the basis of these estimates, which confirm the existence of network externalities, the paper discusses several policies that could result in a permanent decrease in dollarization.